2012
DOI: 10.3892/ijmm.2012.979
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin attenuates the release of pro-inflammatory mediators from lipopolysaccharide-stimulated BV2 microglia by inactivating nuclear factor-κB and inhibiting mitogen-activated protein kinases

Abstract: Abstract. Naringenin, one of the most abundant flavonoids in citrus fruits and grapefruits, has been reported to exhibit anti-inflammatory and antitumor activities. However, the cellular and molecular mechanisms underlying the naringenin anti-inflammatory activity are poorly understood. In this study, we conducted an investigation of the inhibitory effects of naringenin on the production of lipopolysaccharide (LPS)-induced pro-inflammatory mediators in BV2 microglial cells. We found that pre-treatment with nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Our experiments demonstrated that naringenin exerted antagonistic effects on LPS-induced TNF-α and IL-6 expression in murine macrophages. Such results are in accordance with previous reports that showed that naringenin inhibits the production of proinflammatory cytokines and chemokines in LPS-stimulated epithelial cells and microglia cells1617. Moreover, naringenin demonstrated inhibitory activity against enzymes (iNOS, COX-2 and NOX2), which are responsible for the production of secondary mediators in macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…Our experiments demonstrated that naringenin exerted antagonistic effects on LPS-induced TNF-α and IL-6 expression in murine macrophages. Such results are in accordance with previous reports that showed that naringenin inhibits the production of proinflammatory cytokines and chemokines in LPS-stimulated epithelial cells and microglia cells1617. Moreover, naringenin demonstrated inhibitory activity against enzymes (iNOS, COX-2 and NOX2), which are responsible for the production of secondary mediators in macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…The study here showed that flavanones present an important inhibition of NO production in macrophages stimulated with LPS. This accentuates the anti-inflammatory role of native and processed naringenins and accords with other researchers who showed the immunomodulatory effect of NG (Bodet et al 2008;Lopez-Posadas et al 2008;Park et al 2012;Yilma et al 2013). On the other hand, the oxidation of DCFH-DA by peroxyl radicals was significantly inhibited by NG in macrophages and by hNG in splenocytes.…”
Section: Discussionsupporting
confidence: 91%
“…Flavonoids are well known to be anti-inflammatory in this cell line [38, 39]. Therefore, to evaluate the contribution of putative nicotinic activity, their effects were blocked with MLA.…”
Section: Resultsmentioning
confidence: 99%